Haus-Rucker-Co LIVE! and Commoning the Museum. Issue 1 (2nd January 2019) - Elfline, Ross
Abstract: In 1970, the Museum of Contemporary Crafts in New York City hosted the exhibition Haus-Rucker-Co LIVE!, a mid-career retrospective of the Viennese architectural collective. Most historians have studied the range of design works created by the trio—and featured in the exhibition—alongside contemporaneous architects' concerns with sci-fi fantasy; temporary, inflatable structures; and countercultural liberation. While not ignoring the emancipatory potential of these works, this essay focuses primarily on the set of performative actions Haus-Rucker-Co staged within the museum during the run of the exhibition, including: their decision to live within the museum galleries, the hosting of weekly meals in the exhibition space, and the ritual devouring of a scale model of the museum made out of cake. Taken together, these acts foreground a sense of sociality and community that counters the museum's standard emphasis on individualized aesthetic absorption.